Sędziowie śledczy do spraw wyjątkowego znaczenia w II Rzeczypospolitej - Koredczuk, Józef (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
Investigating judges for matters of special importance, established in 1927, did not draw on the French model of investigating judges we found in the Code of the Criminal Procedure, but on the Russian model providing for judges for matters of special importance. They were judges in charge of proceedings in the most diffi cult, complicated, especially important cases beyond the competence of district investigating judges. With time they were also entrusted with political cases (e.g. of individuals accused in the Brest trials). The judges not only presided over proceedings of special importance, but also had a unique legal status. They were appointed at the Court of Appeal, but were subordinated to the Minister of Justice (Chief Prosecutor), who decided which cases would be entrusted to them, which made the institution not only unique but also political.
Keywords: kodeks postępowania karnego; Minister Sprawiedliwości; prawo o ustroju sądów powszechnych; Sąd Apelacyjny; sędzia śledczy; sędzia śledczy w sprawach o szczególnym znaczeniu